ℋ∞ Stability Conditions for Fuzzy Neural Networks - Choon Ki Ahn (Advances in Fuzzy Systems)
This paper presents a novel approach to assess the stability of fuzzy neural networks. First, we propose a new condition for the ℋ∞ stability of fuzzy neural networks. Second, a new ℋ∞ stability condition based on linear matrix inequality (LMI) is presented for fuzzy neural networks. These conditions also ensure asymptotic stability without external input.